Chapter 7. Cucurbit Production - Josh H. Freeman; Eugene J. McAvoy; Craig Frey; Nathan S. Boyd; Mathews L. Paret; Qingren Wang; Johan Desaeger; Jawwad Qureshi; Xavier Martini; Phillip B. Williams (EDIS)
Chapter 7 of the Vegetable Production Handbook.